Effect of Hemodialysis on Hepatic Cytochrome P450 Functional Expression - Josée Michaud; Thomas D. Nolin; Judith Naud; Mélina Dani; Jean-Philippe Lafrance; Francois A. Leblond; Jonathan Himmelfarb; Vincent Pichette (Journal of Pharmacological Sciences, 2008)
Cytochrome P450 (CYP) functional expression is reduced in uremia and normalized after restoration of kidney function via transplantation. The aim of this study was to evaluate the effect of conventional hemodialysis on the functional expression of CYP1A, 2C, and 3A. We also investigated the role of nuclear factor-κB (NF-κB) in CYP regulation during uremia. Primary cultures of normal rat hepatocytes were incubated with serum obtained from end-stage renal disease patients pre- and post-hemodialysis and healthy control subjects, in the presence and absence of the NF-κB inhibitor andrographolide. Uremic pre-hemodialysis serum caused significant reductions (P<0.01) in CYP1A (44%), 2C (27%), and 3A (35%) protein expression compared to control serum, while dialyzed serum (i.e., obtained immediately post-hemodialysis) had no effect. CYP1A2, 2C11, and 3A2 mRNA expression, as well as CYP3A activity, were similarly impacted by uremic serum and were improved to >80% of control values after hemodialysis. NF-κB inhibition nearly eliminated the effect of uremic serum on CYP functional expression. This is the first study to demonstrate that conventional hemodialysis acutely improves altered CYP functional expression observed in rat hepatocytes incubated with uremic human serum. Keywords:: hemodialysis, end-stage renal disease, cytochrome P450, gene expression, drug metabolism